Social structure and politics: studies in independent India - Ooman, T.K. (Delhi, 1984)
SOCIAL STRUCTURE AND POLITICS analyzes the relationship between society and polity with special reference to independent India. The twelve essays in the volume attempt to explore themes such as social structure and political processes, community power struc ture, Green Revolution and agrarian tensions, and student power and politics. The book provides a macro perspective on Indian society and polity as well as deals with micro structures and processes. It presents new empirical facts, examines the existing concepts, and advances new theoretical propositions. It would be valuable for students of social science in general and of sociology and political science in particular. It contains much that can sensitize the politician, the policy maker, the development administrator and the lay reader about some of the import ant problems of independent India.
Keywords: Social classes